A brief history of tuberculosis in the Czech Lands - Vargová, Lenka; Vymazalová, Kateřina; Horáčková, Ladislava (Tuberculosis (Edinburgh, Scotland), 2017)
Tuberculosis currently remains a serious medical problem, therefore increased attention is being paid to this disease. Paleopathological studies focused on the monitoring of morbid changes in skeletal remains of historical populations facilitate a detailed study of the development of this disease. They provide direct evidence of the existence of tuberculosis and its past forms. In addition to literary and iconographic sources, the present study is focused on recording the findings of bone tuberculosis in historical osteological sets from the Czech Lands and is the starting point for their detailed review. Approximately 76 cases of bone tuberculosis from the Czech Lands have been published and more or less reliably documented from 20 archeological sites dated back from the Eneolithic to the modern period.
Keywords: History, 17th Century; Specific inflammation; mužské pohlaví; paleopatologie; Male; Czech Republic; History, 20th Century; Central Europe; dějiny 16. století; Skeletal remains; Female; Humans; History, Medieval; Paleopathology; dějiny 15. století; dějiny 17. století; History, 16th Century; lidé; bakteriologické techniky; ženské pohlaví; vakcíny proti tuberkulóze; History, 19th Century; Tuberculosis Vaccines; Česká republika; dějiny 18. století; Prevalence; dějiny 20. století; History, 18th Century; History, 21st Century; tuberkulóza osteoartikulární; dějiny 19. století; Bacteriological Techniques; dějiny středověku; History, 15th Century; Československo; Czechoslovakia; Mycobacterium tuberculosis; dějiny 21. století; History, Ancient; Tuberculosis, Osteoarticular; prevalence; dějiny starověku